COMUM URBANO: A CIDADE ALÉM DO PÚBLICO E DO PRIVADO - Joao Bosco Moura Tonucci Filho (2017)
This research aimed to overcome the theoretical dissociation between the commons and the urban. In general, the commons refers to goods, spaces and resources that are shared, used and managed collectively through practices developed by the community itself, outside the scope of the State and the market. In different metropolises around the world, the commons has been invoked politically by social movements, activists and researchers both in resistance to the enclosures, privatizations and dispossessions associated with neoliberal capitalism, as in experiences of construction of autonomous spaces. However, the theorists of the commons did not propose, with rare exceptions, to discuss more thoroughly what it would be like to look at contemporary urbanization from a commons perspective, and vice versa. Therefore, in order to theoretically urbanize the commons, it was necessary, first, to investigate the emergency contexts, the senses and the histories of the commons, as well as to expose and evaluate its main critical approaches, highlighting their relations with property rights. The most recent literature dealing with the urban commons has also been debated, encompassing studies ranging from common resources in the city, with its collective property arrangements and diverse communities, to those who treat the city itself as a commons. In addition, those studies that recognize peripheral spaces of the global South by sustaining informal practices of communality and cooperation were emphasized. In order to face the theoretical challenges of conceiving the commons in its urban dimension, I proposed an elaboration anchored in the thought of Henri Lefebvre. The lefebvrian urban, characterized by its character of centrality, mediation and difference, plus the emancipatory promise of the city, becomes understood as a contradictory space of enclosure and production of the commons. More broadly, it is the very production of space, made central in the contemporary world to the reproduction of capitalist social relations, which increasingly implies the struggle for appropriation of space itself as a commons. Finally, the potentials and impasses of this urban commons in the periphery of the Brazilian metropolis were illustrated by the recent experience of housing occupations in Belo Horizonte, particularly with respect to the contradiction between the wealth of common production practices that question the hegemony of private property and pressures of the proprietary order. Thus, the urban commons that emerges from the research points to experiences of space production that, gestated in everyday life and based on relations and practices of cooperation, collective appropriation, use and self-management, converge towards the realization of the right to the city, beyond the public and the private.